Microscopic and Surface Properties of K-Na Liquid Alloys - Koirala, I.; Singh, B. P.; Jha, I. S. (Himalayan Physics, 2013)
The deviation from ideal mixture behavior and concentration dependent symmetry in the microscopic and surface properties of K-Na liquid alloy is investigated within a simple statistical model. The concentration dependent of microscopic functions(concentration fluctuation in the long wavelength limit, Warren-Cowley short range order parameter) and surface properties(surface concentration and surface tension) has got special attention to show a tendency of like atom pairing in the mixture. The theoretical analysis reveals that energy parameter is temperature dependent, K-Na alloys is of weakly interacting system and K-atoms segregates on the surface of K-Na liquid alloys at bulk concentration of Na. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 40-45 Uploaded date: 12/23/2013